Short-term outcomes of mothers and infants exposed to antenatal amphetamines. Issue 1 (13th August 2009) - Oei, J; Abdel-Latif, M E; Clark, R; Craig, F; Lui, K
Abstract : Aim: To determine the short-term outcomes of newborn infants and mothers exposed to antenatal amphetamines in the state of New South Wales and the Australian Capital Territory during 2004. Methods: Amphetamine exposure was determined retrospectively using ICD-10 AM morbidity code searches of hospital medical records and from records of local drug and alcohol services. Records were reviewed on site. All public hospitals (n = 101) with obstetric services were included. Results: Amphetamines were used by 200 (22.9%) of the 871 identified drug-using mothers. Most women (182, 91%) injected amphetamines intravenously. Compared with the other 669 drug users, amphetamine-using mothers were significantly more likely to use multiple classes of drugs (45.0% vs 7.8%), be subject to domestic violence (32.1% vs 17.5%), be homeless (14.8% vs 4.9%) and be involved with correctional services (19.8% vs 9.7%). The incidence of comorbid psychiatric illnesses were significantly higher (57.4% vs 41.7%) and their infants were more likely to be preterm (29.5% vs 20.4%), notified as children at risk (67.0% vs 32.8%), fostered before hospital discharge (14.5% vs 5.5%) and less likely to be breastfed (27.0% vs 41.6%). Conclusions: Amphetamine-exposed mothers and infants in public hospitals of NSW and the ACT are at significantly higher risk of adverse social and perinatal outcomes even when compared with mothers and infants exposed to other drugs of dependency. Increased vigilance for amphetamine exposure is recommended due to a high prevalence of use, especially in Australia, as a recreational drug.